6x+4x+4+8=7x+3+2x

Simple and best practice solution for 6x+4x+4+8=7x+3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4x+4+8=7x+3+2x equation:


Simplifying
6x + 4x + 4 + 8 = 7x + 3 + 2x

Reorder the terms:
4 + 8 + 6x + 4x = 7x + 3 + 2x

Combine like terms: 4 + 8 = 12
12 + 6x + 4x = 7x + 3 + 2x

Combine like terms: 6x + 4x = 10x
12 + 10x = 7x + 3 + 2x

Reorder the terms:
12 + 10x = 3 + 7x + 2x

Combine like terms: 7x + 2x = 9x
12 + 10x = 3 + 9x

Solving
12 + 10x = 3 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
12 + 10x + -9x = 3 + 9x + -9x

Combine like terms: 10x + -9x = 1x
12 + 1x = 3 + 9x + -9x

Combine like terms: 9x + -9x = 0
12 + 1x = 3 + 0
12 + 1x = 3

Add '-12' to each side of the equation.
12 + -12 + 1x = 3 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 3 + -12
1x = 3 + -12

Combine like terms: 3 + -12 = -9
1x = -9

Divide each side by '1'.
x = -9

Simplifying
x = -9

See similar equations:

| 4x+5+2x=31 | | -44=-8(-2x+4) | | 4x+2y-3z+a=14 | | -94=8r+3(6-8r) | | (2j+3)-4j-(j+3)= | | 2x-3y+z+5a=-9 | | 2x^2-3px-p=0 | | 3x+15=17+x | | 330=-6(1-7x) | | sinx=0.359 | | 2x(2y-11)=80 | | x+5y=3y-2 | | 2n-8(1+3n)=-96 | | -137=-4(1+8m)-5 | | -137=-4(1+8m) | | 17x-3=3x | | 4x+32=-48 | | 84=-4(3+8x) | | 170=-5(1-7n) | | -5(6+2r)-3r=-108 | | 3m=m+10 | | 464=4k-8(8k+2) | | 200=8(1+8n) | | 136=-3(1-7x)-8 | | h(x)=-16x^2+32x+4 | | 85=-6(k-6)-k | | 1x+3y=7.25 | | 6(-8+3a)=-102 | | 154=7(1-3b) | | -91=-7(x+5) | | 5(-3n+5)-3n=-101 | | -4(8p-8)=-160 |

Equations solver categories